Effect of Dietary Supplementation of Garlic Along with Multi-strain Probiotic on Growth Performance, Relative Organ Weights, Intestinal Morphology, Caecal Microflora and Serum Profile of Broiler Chicken - Shrestha, Reema (Indian Journal of Animal Nutrition, 2021)
The present study was conducted to evaluate the effects of feeding garlic along with multi-strain probiotics on performance of broilers. One hundred eighty no. (N=180) of day old commercial Ven Cobb 50 broiler chicks 45 chicks in each group with 3 replicates of 15 chicks each by following Randomized Block Design(RBD) and chicks were randomly distributed into 4 treatment groups i.e.T0, T1, T2 and T3 on the basis of their body weight. Experimental diets were formulated for starter and finisher phases to meet the nutrient requirement as per ICAR (2013) using commonly available ingredient. A corn and soybean meal based diet was used as the control diet (T0). The experimental diets were formulated by mixing the basal diet with garlic powder (GP) and multi-strain probiotics (MSP) at 0.25, 0.50 or 0.75% (GP+MSP) in diets of groups T1, T2 and T3,respectively. daily weight gain and feed conversion ratio (FCR) was significantly (Pdâ€0.05) improved in T2 group as compared to other group. Jejunal villus height and villus width was significantly (P